2013
DOI: 10.1155/2013/507539
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation in Sepsis: The Role of Endotoxin Removal by Polymyxin B-Immobilized Cartridge

Abstract: Severe sepsis results in high morbidity and mortality. Immunomodulation strategies could be an adjunctive therapy to treat sepsis. Endotoxin is a component of gram-negative bacteria and plays an important role in the pathogenesis of septic shock when it is recognized by immune cells. Removal of endotoxin could be an effective adjunctive approach to the management of sepsis. Devices to adsorb endotoxin or inflammatory cytokines have been designed as a strategy to treat severe sepsis, especially sepsis caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 98 publications
0
55
0
1
Order By: Relevance
“…Bakulev NSPCCS in 2009-2016, showed the safety and efficacy of the combined therapies mentioned above. [53,54] We observed that the combination of LPS-adsorption and HDF filters with high cut-off EMiC2 membranes led to a 34% MAP increase [from 76 (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81) to 90 (85-102) mmHg, P < 0.001] with reduced vasopressor and inotropic support. The increase in MAP during LPS-adsorption with CPFA was 12% with the significant decrease in vasopressor support [the dose of noradrenaline was halved from 0.2 (0.15-0.3) to 0.1 (0.05-0.15) µg/kg/min, P = 0.024].…”
Section: Extracorporeal Blood Purification In Complex Intensive Theramentioning
confidence: 87%
See 1 more Smart Citation
“…Bakulev NSPCCS in 2009-2016, showed the safety and efficacy of the combined therapies mentioned above. [53,54] We observed that the combination of LPS-adsorption and HDF filters with high cut-off EMiC2 membranes led to a 34% MAP increase [from 76 (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81) to 90 (85-102) mmHg, P < 0.001] with reduced vasopressor and inotropic support. The increase in MAP during LPS-adsorption with CPFA was 12% with the significant decrease in vasopressor support [the dose of noradrenaline was halved from 0.2 (0.15-0.3) to 0.1 (0.05-0.15) µg/kg/min, P = 0.024].…”
Section: Extracorporeal Blood Purification In Complex Intensive Theramentioning
confidence: 87%
“…[64][65][66][67] LPS-adsorption using Toraymyxin-PMX-20R Polymyxin B immobilized fiber cartridges was found to be effective, simultaneously acting through sorption and apheresis on bacterial endotoxin, systemic inflammatory mediators and activated immune cells. [59][60][61]68,69] CPFA performs an immunomodulatory role by acting on inflammatory mediators (interleukin-1β, -6, -8, -10, -18, tumor necrosis factor-α and others) via various mass transfer mechanisms such as diffusion, convection and adsorption. The advantages of CPFA include the passage of plasma (and not blood) through the sorption column, which increases the contact time with the sorption surface and improves the efficiency of the procedure.…”
Section: Extracorporeal Blood Purification In Complex Intensive Theramentioning
confidence: 99%
“…Discussing the possibility of immunomodulation during selective LPS adsorption, some researchers explain immunomodulation by direct endotoxin elimination (mediated mechanism) [30]. Other researchers are of the opinion that circulating cytokines and growth factors are removed directly, as they present in the eluate from used PMX cartridge fibres after the procedure [31].…”
Section: Discussionmentioning
confidence: 99%
“…Extracorporeal support systems may serve as cytokine removal facilities (44). Polymyxin B-immobilized cartridge has been successfully used in endotoxin elimination (49). CytoSorb® is effective in reducing postoperative systemic inflammatory response syndrome.…”
Section: Il-6 Removalmentioning
confidence: 99%